FAKTOR PSIKOLOGIS DAN KEPERCAYAAN DALAM KEPUTUSAN PEMBELIAN PRODUK KOSMETIK - Irna Febryanty; Budi Suryowati (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
This study aims to determine how the psychological influence of motivation, perception, and belief on purchasing decisions of Emina Cosmetics products in Jakarta. The study was conducted on women who buy and use Emina cosmetic products. The number of samples taken was 100 respondents using the purposive sampling technique. Data were collected through the distribution of questionnaires. The analytical method used is PLS-SEM (Partial Least Square-Structural Equation Modeling) using SmartPLS 3.0 software. The results showed that the psychological variables that had an effect on the purchasing decisions of Emina products were the motivation and belief variables and the perception variables had no effect on the purchasing decisions of Emina products in Jakarta